Sistemas de Cobros y Recuperación de la cartera vencida de la Empresa Pública Municipal de Mercados, Centros Comerciales y Bahías del Cantón Babahoyo - Guzmán Morán, Ginger Gabriela (2019)
The Municipal Public Company of Markets, Shopping Centers and Bays of the Babahoyo Canton, is located in Av. General Barona between the streets 27 de Mayo and Abdón Calderón, the same one that despite having its legal autonomy, is part of the Autonomous Government Decentralized Municipal Babahoyo Canton. As a company, it seeks to provide a better service to the community through the markets, shopping centers and bays of the canton.